Online disinformation in the run-up to the Indian 2019 election - Das, A; Schroeder, R (Routledge, 2020)
This essay examines the role of disinformation in the Indian general election of 2019. The findings are presented against the background of previous work on the role of digital media in Indian politics. The essay uses 25 in-depth interviews among ordinary Indians to probe their level of awareness about so-called ‘fake news’. It also examines their behavior in seeking news and sharing political information and their views about the digital campaign strategies of leaders and parties. The interviewees were concerned about the increasing role of religious extremism online. Yet they were also strongly aware of the role of disinformation campaigns and had strategies for working around being misled by information shared on social media. The essay concludes by assessing how disinformation and online extremism are likely to have affected the 2019 election, and makes comparisons with Modi's election in 2014 and with other leaders.